Evaluation of DNA extraction in Iraqi Rheumatoid Arthritis Patients - Eman Shaker Ali; Aliaa Saadoon Abdul Razzaq Al-Faraji (International Journal of Medical Toxicology and Legal Medicine, 2024)
The present study aims to highlight on role of DNA extraction and purity of DNA In Iraqi patients with Rheumatoid Arthritis (RA). In order to achieve that, 50 patients of both gender with RA. Another 50 individuals were selected as the Healthy control of both gender, with the age average of (20-40)years . The measured concentration and purity of DNA after DNA extraction . The obtained results after comparing patients with the healthy groups indicated DNA purity in patients and healthy control, there was no effect in RA disease in the present study. Extraction of high quality DNA with minimum time and cost will is use of interest in molecular genetic studies in Rheumatoid Arthritis patients (RA).Protein tyrosine phosphatase non-receptor type 22 (lymphoid), also recognized as PTPN22, is a protein encoded by the PTPN22 gene .